2015
DOI: 10.1002/bkcs.10225
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrazolo[1,5‐a]quinolines from 1‐Aryl‐5‐styrylpyrazoles via Intramolecular Friedel‐Crafts Reaction/Aerobic Oxidation

Abstract: Various pyrazolo[1,5‐a]quinolines were synthesized via the intramolecular Friedel‐Crafts reaction of 1‐aryl‐5‐styrylpyrazoles and the following base‐catalyzed aerobic oxidation process. The required 1‐aryl‐5‐styrylpyrazoles were readily prepared from the corresponding conjugated dienones and arylhydrazines in a one‐pot process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…During our recent interest in IMFC reactions and the chemical transformations of isatin derivatives, we reasoned out that pyrrolo[3,2,1‐ ij ]quinoline‐1,2‐diones could be prepared via an IMFC approach as shown in Scheme (Eq. (3)).…”
Section: Methodsmentioning
confidence: 99%
“…During our recent interest in IMFC reactions and the chemical transformations of isatin derivatives, we reasoned out that pyrrolo[3,2,1‐ ij ]quinoline‐1,2‐diones could be prepared via an IMFC approach as shown in Scheme (Eq. (3)).…”
Section: Methodsmentioning
confidence: 99%
“…The base-catalyzed aerobic oxidation of dihydropyrazolo[1,5-a]quinolines 126 afforded the corresponding pyrazolo[1,5-a]quinolines 127 (Scheme 38, ii). However, the reaction only occurred when R 5 = Ph and R 6 = H [87]. In 2015, Moon et al reported the acid-catalyzed intramolecular Friedel-Crafts (IMFC) reaction of several 1-aryl-5-styrylpyrazoles 125 in the presence of PPA to produce dihydropyrazolo[1,5a]quinolines 126 (Scheme 38, i) [87].…”
Section: Transformations Of 4-styrylpyrazolesmentioning
confidence: 99%
“…However, the reaction only occurred when R 5 = Ph and R 6 = H [87]. In 2015, Moon et al reported the acid-catalyzed intramolecular Friedel-Crafts (IMFC) reaction of several 1-aryl-5-styrylpyrazoles 125 in the presence of PPA to produce dihydropyrazolo[1,5a]quinolines 126 (Scheme 38, i) [87]. It is worth mentioning that the corresponding five-membered ring product was not obtained.…”
Section: Transformations Of 4-styrylpyrazolesmentioning
confidence: 99%
See 2 more Smart Citations